All-solid-state Lead(II)–Selective Potentiometric Sensor Based on 9,10-dibromo-2-(propylthio)anthracene-1,4-dione - Kıymet Berkil Akar; Oğuz Özbek; Abdulkadir Akyasan; Ömer Işıldak (Journal of Advanced Research in Natural and Applied Sciences)
Ion-selective sensors are widely used in routine analysis of ionic species. In this research, a highly selective potentiometric sensor was developed, which is sensitive against Pb2+ ions compared to other common inorganic cations. The optimum composition of the developed sensor was determined to be as 3.0% ionophore, 64.0% bis(2–ethylhexyl)adipate (DEHA), 32.0% poly (vinyl chloride) (PVC), and 1.0% anion excluder (KTpClPB). The Pb2+–selective sensor had a Nernstian response of 28.7±2.2 mV/decade over a wide linear range of 1.0×10-5–1.0×10-1 M and a low detection limit of 2.77×10-6 M. The newly developed sensor worked over a wide pH range (4.0–10.0), and the response time was short (7s). The sensor, which had good reproducibility, was applied to various water samples and determined Pb2+ ions with very high recoveries.